Performance analysis of optimized controllers with bio-inspired algorithms - Ibarra Alexander; Caiza Daniel; Ayala Paul; Arcos-Aviles Diego (Institute of Advanced Engineering and Science, 2020)
This article proposes tuning of PID controllers through optimization techniques known as collective intelligence algorithms: the colony of ants and cuckoo search, applied to the temperature control of a PCT-2 plant. The dynamic behavior analysis of the controllers tuned by the application of collective intelligence algorithms were performed in comparison to a controller tuned by the genetic algorithm method and a controller designed with the PID tuner tool, obtaining favorable results in the tuning of the algorithms cuckoo search and ants colony in comparison to the PID tuner method and with a faster execution speed than the genetic algorithms method.